A compreensão oral em inglês por meio de filmes em DVD: a percepção de alunos sobre uma unidade didática - Tonetti, Antonieta Cristina Simonato (2007)
This research aims at investigating how a language learning material using DVD films can contribute to the development of the listening comprehension and the learning process of a public school group of students. The material was designed according to the teaching-learning and language approaches suggested by Parâmetros Curriculares Nacionais Língua Estrangeira (Brasil, 1998). The theoretical bases for this study are the Parâmetros Curriculares Nacionais Língua Estrangeira (Brasil, 1998), the sociointeractionist view suggested by Vygotsky (1934/1998). Theories of the listening comprehension process defended by Ellis (2003), Rost (2002), Vandergrift (1999), Richards (1999), Anderson e Lynch (1988) and the use of films for the development of the listening comprehension process by Luo (2004), King (2002), Katchen (2001) Cunning (2001), Stempleski & Tomalin, (2001), Thanajaro (2000) and Chung (1999) were relevant to this research. This study was conducted in the teacher-researcher s classroom with 15 students of the 2nd High School grade of a public school in Santos. The data were collected in the second semester of 2005 by perceptive questionnaires, an interview and teacher s reflective diaries. The results showed that the language learning material with DVD films can contribute to the learning and the development of listening comprehension process of public school group of students